Counter Discourse of Power in Indonesian narrative texts - Latjuba, Ade Yolanda (Advances in Social Sciences Research Journal, 2014)
Abstract This study aims to examine and develop an investigation method for language data from a discourse found in a previous study. The object of research is in the form of Indonesian narrative text dated early 20th century. First of all, the method of obtaining discourse language data focusing on “power” Nodal Point (NP) was examined. When the results revealed some similarities and a few differences, several questions investigating language data were developed by focusing on slightly different NP, that is “counter discourse of power”. After discussing the context and describes what is contained in the Indonesian narrative texts, the results reveal that power discourse in Indonesian narrative texts was still a continuity of power discourse in colonial texts, with a little difference in emphasis. Furthermore, language data investigated from “counter discourse of power” show that the Indonesian narrative texts contained criticism toward tradition and people who followed the western way of life. Keywords: investigation method, counter discourse of power, context, criticism on custom